2015
DOI: 10.1016/j.cmet.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Mitochondrial Transhydrogenase Causes Oxidative Stress in Heart Failure

Abstract: Mitochondrial reactive oxygen species (ROS) play a central role in most aging-related diseases. ROS are produced at the respiratory chain that demands NADH for electron transport and are eliminated by enzymes that require NADPH. The nicotinamide nucleotide transhydrogenase (Nnt) is considered a key antioxidative enzyme based on its ability to regenerate NADPH from NADH. Here, we show that pathological metabolic demand reverses the direction of the Nnt, consuming NADPH to support NADH and ATP production, but at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
316
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(351 citation statements)
references
References 43 publications
14
316
2
Order By: Relevance
“…29 In cardiac mitochondria, IDH2 is the major source of the mitochondrial NADPH required for glutathione production and thioredoxin recycling. 40 Therefore, Epac1-mediated inhibition of IDH2 impaired NADPH production, hence, decreased the antioxidant capabilities of the cardiomyocytes during HX+R. We extended our work to identify the signaling pathway that accounted for Epac1-inhibited IDH2.…”
Section: Discussionmentioning
confidence: 79%
“…29 In cardiac mitochondria, IDH2 is the major source of the mitochondrial NADPH required for glutathione production and thioredoxin recycling. 40 Therefore, Epac1-mediated inhibition of IDH2 impaired NADPH production, hence, decreased the antioxidant capabilities of the cardiomyocytes during HX+R. We extended our work to identify the signaling pathway that accounted for Epac1-inhibited IDH2.…”
Section: Discussionmentioning
confidence: 79%
“…In general, previous work has shown that there is an inverse relationship between maintenance of redox and energetic balance in the heart, related to the NADH versus NADPH levels. 41 To preserve an optimized proportion between mitochondrial respiration and ROS emission, a reduced mitochondrial matrix environment as observed in this study, thus, might be critical.…”
Section: Discussionmentioning
confidence: 95%
“…A recent essay (Kraev 2014) summarizes concerns over atypical stress responses in C57BL/6J mice potentially resulting from a null genotype for the Nnt gene, which encodes the enzyme nicotinamide nucleotide transhydrogenase. This mitochondrial enzyme increases the production of reactive oxygen species (ROS) under stressful conditions, so that its elimination appears protective (Nickel et al 2015). It was suggested that experiments related to stress responses be repeated in closely related C57BL/6N mice or other substrains that carry functioning Nnt alleles.…”
Section: C57bl/6mentioning
confidence: 99%